Doxomysis algoensis, a new mysid species (Crustacea, Mysidacea) from Algoa Bay (South Africa) - Wooldridge, T. H.; Mees, J. (Hydrobiologia, 2000)
Doxomysis algoaensis sp.nov. is described from Algoa Bay, South Africa where it is common in nearshore marine waters just beyond the breaker line. D. algoaensis sp.nov. is morphologically similar to D. australiensis, but can readily be distinguished by the shape and armature of the telson and the length of the exopod of the fourth male pleopod. The apical cleft is one fifth the telson length in the former species and one third the length in D. australiensis. The telson apex on each side of the cleft is also armed with five and four stout spines in the two species, respectively. In D. australiensis, the exopod of the fourth male pleopod is almost three times the length of the endopod; in D. algoaensis sp.nov., the exopod is only slightly longer than the endopod. Other distinctive features of D. algoaensis sp.nov. include the maxillary palp, which is only slightly broader than long and the greater number of spines on the endopod of the uropod.
NeMys doc_id: 3545